Driving forces of social media and its impact on tourists’ destination decisions: a uses and gratification theory - Solomon A. Keelson; Emmanuel Bruce; Sulemana Bankuoru Egala; John Amoah; Abdul Bashiru Jibril (Cogent Social Sciences)
This study investigates the impact of social media on tourists’ destination decisions in a less digitalized economy through the lens of the uses and gratification theory. Data was collected from 428 local tourists sampled across various tourist destinations in Ghana (a sub-Sahara Africa) using a structured questionnaire. Analysis was carried out using variance-based PLS-SEM (Partial Least Square Structural Equation Modelling). The results show that tourist contentment, destination image, behavioral goals, and the availability of tourism information are driving forces of social media usage toward tourism destination decisions. The findings imply that tourism service providers should revise and incorporate the trending social media strategies to enhance their interaction with prospective visitors (customers) to increase their market share and become more competitive. This paper not only broadens the social media marketing literature but offers a comprehensive assessment of the integration of social media given the myriad of challenges besetting users and tourism service providers and discusses its impact in shaping tourist destination decisions in emerging and developing economies. Limitations and avenues for future research are discussed.